ANALISIS UPAH PEKERJA INDUSTRI OLAHAN SINGKONG NGAGLIK SALATIGA DENGAN PENDEKATAN STOLPER-SAMUELSON - Trisnawati, Lelyko; Pratomo, Yulius (Buletin Studi Ekonomi; VOL.24.NO.2.AGUSTUS 2019DO - 10.24843/BSE.2019.v24.i02.p02, 2019)
Abstract: Analysis of Wages of Ngaglik Salatiga Cassava Processed Industry Workers With the Stolper-Samuelson Approach. This study aims to see the magnitude of the effect of increasing product prices on labor wages used to produce those outputs. The study was conducted on cassava processing industry in Ngaglik Salatiga. The data used for the analysis are cross-section data of 53 respondents (saturation sampling). Data were analyzed using multiple regression tools. The main result of the study shows that output prices have a positive effect on labor wages. Every one percent increase in output prices will increase labor wages by 7.95 percent. Keywords: output price; wage; Stolper-Samuelson Theorm.